The respon of IKIP Budi Utomo students toward the instructional book of cell biology subject aided by interactive multimedia - Hartati, Tri Asih Wahyu; Safitri, Dini (University of Muhammadiyah Malang, 2017)
The development of Science and Technology (Science and Technology) takes place very rapidly. The development of science and technology will impact on graduate competency changes desired by the industry. This change of course will be followed by updating the curriculum, learning resources and teaching materials are used, one of them teaching materials on the subjects of Cell Biology. In the course of Cell Biology, the students only take textbooks without the support of interactive multimedia. Good teaching materials is the teaching materials arranged in a systematic, according to the needs and character of students, as well as validated by the teaching materials. The purpose of this study was to determine response Â students Biology Education IKIP Budi Utomo against Cell Biology course textbook aided interactive multimedia. The development method used is the 4D model consisting of stages define, design, develop, and disseminate. This study is limited to the stages develop. Legibility test results showed that students responded well teaching materials and provide proper assessment of the teaching materials.